Penerapan manajemen risiko untuk meminimalisir kerugian dalam usaha kecil dan menengah - Hariyono, Bunga Prameswari (Maliki Interdisciplinary Journal, 2025)
Small and Medium Enterprises (SMEs) play a vital role in the national economy but often face challenges such as financial losses and market uncertainties. This article aims to analyze how the application of risk management can help SMEs minimize losses and enhance business resilience. The study employs a qualitative-descriptive approach through literature reviews and case studies of selected SMEs that have implemented risk management strategies. The findings reveal that systematic risk identification and management—including financial, operational, reputational, legal, and market risks—significantly contribute to business stability and growth. Moreover, awareness, training, and external support are crucial factors in the successful implementation of risk management in the SME sector. This article is expected to provide practical insights for SME owners in building resilient and sustainable businesses.